2017
DOI: 10.1097/shk.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Gas Protects Against Intestinal Injury in Wild Type But Not NRF2 Knockout Mice With Severe Sepsis by Regulating HO-1 and HMGB1 Release

Abstract: The intestine plays an important role in the pathogenesis of sepsis. Hydrogen gas (H2), which has anti-oxidative, anti-inflammatory, and anti-apoptotic effects, can be effectively used to treat septic mice. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a redox-sensitive master switch that regulates the expression of antioxidant and protective enzymes. This study investigated the effects of 2% H2 on intestinal injuries and the underlying mechanisms in a mouse model of severe sepsis. Male Nrf2 knockout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 25 publications
3
42
0
2
Order By: Relevance
“…In our study, H 2 treatment significantly up‐regulated the expression of Nrf2 and its downstream targets such as HO‐1, NQO1 and AKR1C1 in wound tissue and HUEVCs exposed to H 2 O 2 . Similar phenomena were also observed in previous studies of other organ I/R injury or other inflammatory diseases . Molecular hydrogen could attenuate intestinal injury in wild‐type but not NRF2‐knockout mice with severe sepsis by regulating HO‐1 expression .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, H 2 treatment significantly up‐regulated the expression of Nrf2 and its downstream targets such as HO‐1, NQO1 and AKR1C1 in wound tissue and HUEVCs exposed to H 2 O 2 . Similar phenomena were also observed in previous studies of other organ I/R injury or other inflammatory diseases . Molecular hydrogen could attenuate intestinal injury in wild‐type but not NRF2‐knockout mice with severe sepsis by regulating HO‐1 expression .…”
Section: Discussionsupporting
confidence: 87%
“…Similar phenomena were also observed in previous studies of other organ I/R injury or other inflammatory diseases . Molecular hydrogen could attenuate intestinal injury in wild‐type but not NRF2‐knockout mice with severe sepsis by regulating HO‐1 expression . Therefore, hydrogen might activate the Nrf2/ARE pathway to restore the homoeostasis of cutaneous oxidation‐reduction system against I/R injury.…”
Section: Discussionsupporting
confidence: 86%
“…Our previous investigations demonstrated increased survival and reduced injury and dysfunction in different organs (e.g., lungs, liver, kidney, and intestinal tract) in various septic models treated with H 2 inhalation [17][18][19]. In the present study, using a CLP model, we investigated whether HO-1 mediated the positive effects of H 2 on myocardial injury in a murine model of sepsis.…”
Section: Introductionmentioning
confidence: 83%
“…Another study demonstrated that inhalation of 2% H 2 could potentially alleviate intestinal damage caused by severe sepsis by regulating the release of HO-1 and high mobility group box 1 (HMGB1) [16]. Moreover, Nrf2 played a key role in the protective effect of H 2 against intestinal injury [17].…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanisms of neonatal HIBI include oxidative stress, excitability, inflammation, and apoptosis [2]. Many researchers believe that similar to nitric oxide, hydrogen sulfide, and carbon monoxide, H 2 may be an important bioactive gas [30,31]. There are no reported side effects with H 2 , which may confer a unique advantage in disease prevention and treatment [31].…”
mentioning
confidence: 99%